2016
DOI: 10.32607/20758251-2016-8-1-74-81
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antiherpetic Efficiency of Phosphite of Acycloguanosine Ableto Over come the Barrier of Resistance to Acyclovir

Abstract: As has been shown previously, phosphite of acycloguanosine (Hp-ACG) exhibits equal efficacy against ACV-sensitive and ACV-resistant HSV-1 strains in cell culture. Intraperitoneal administration of Hp-ACG to model mice with herpetic encephalitis caused by HSV-1 infection was shown to be effective in protecting against death. In the present work, we continue the study of the antiviral efficiency of Hp-ACG against HSV administered non-invasively; namely in vivo, orally and in the form of ointment formulations. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…The available literature reviewed consistently supports the existence and potentiality of second-line treatments for HSV strains that are resistant to first-line treatments. We have shown that a majority of the studies reviewed have efficacy as potential managements for resistant strains of HSV [1][2][3][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][47][48][49][50][51][52][54][55][56][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][127][128][129]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The available literature reviewed consistently supports the existence and potentiality of second-line treatments for HSV strains that are resistant to first-line treatments. We have shown that a majority of the studies reviewed have efficacy as potential managements for resistant strains of HSV [1][2][3][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][47][48][49][50][51][52][54][55][56][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][127][128][129]…”
Section: Resultsmentioning
confidence: 99%
“…Within this time frame, there were two (1.46%) studies in 2015 [ 6 , 7 ], 15 (10.95%) studies in 2016 [ 1 , 3 , 8 - 20 ], 19 (13.87%) studies in 2017 [ 21 - 39 ], 27 (19.71%) studies in 2018 [ 40 - 64 ], 23 (16.79%) studies in 2019 [ 2 , 65 - 86 ], 24 (17.52%) studies in 2020 [ 87 - 110 ], and 27 (19.70%) studies in 2021 [ 111 - 137 ]. Regarding the type of studies reviewed, 121 (88.32%) studies included in vitro elements [ 2 , 3 , 6 - 12 , 14 - 20 , 23 - 26 , 28 - 42 , 44 - 47 , 49 - 56 , 58 - 64 , 66 , 68 - 72 , 74 - 77 , 79 , 80 , 82 - 87 , 89 - 118 , 120 , 122 - 133 , 135 - 139 ] and 23 (16.79%) in vivo [ 2 , 13 , 15 , 18 , 22 , 25 , 27 , 28 , 37 , 43 , 48 , 56 , 62 , 67 , 73 , 78 , 81 , 100 , …”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…табл. 2) подавляет репродукцию ВПГ-1 в культуре клеток и защищает заражённых животных от гибели при в/б и пероральном введении (на модели генерализованной ГИ мышей); активен при использовании в виде мазевой лекарственной формы [25]. Как отмечалось выше, формирование резистентности вируса к АЦВ в подавляющем большинстве случаев связано с потерей или значительным снижением активности вирусной ТК, что, как правило, обусловливает перекрёстную резистентность вируса ко всем препаратам первого ряда.…”
Section: Introductionunclassified